2013
DOI: 10.1614/ws-d-12-00189.1
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Translocation, and Metabolism of Aminocyclopyrachlor in Tall Fescue (Lolium arundinaceum)

Abstract: Synthetic auxin herbicides are commonly used in forage, pasture, range, and turfgrass settings for dicotyledonous weed control. Aminocyclopyrachlor (AMCP) is a newly developed pyrimidine carboxylic acid with a chemical structure and mode of action similar to the pyridine carboxylic acids—aminopyralid, clopyralid, and picloram. Injury to sensitive dicotyledonous plants has been observed following exposure to monocotyledonous plant material previously treated with pyridine compounds. The absorption, translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 12 publications
9
28
2
1
Order By: Relevance
“…Aminocyclopyrachlor is a pyrimidine carboxylic acid with similar efficacy to pyridine herbicides for weed control in grass crops. Recently, Lewis et al (2013a) reported no metabolism of aminocyclopyrachlor in tall fescue at 192 HAT. Similar results of minimal (<25%) metabolism in tolerant species have been noted with picloram and triclopyr in barley, rice, and wheat (Braverman, 1995; Radosevich and Bayer, 1979; Sharma and Born, 1973).…”
Section: Resultsmentioning
confidence: 99%
“…Aminocyclopyrachlor is a pyrimidine carboxylic acid with similar efficacy to pyridine herbicides for weed control in grass crops. Recently, Lewis et al (2013a) reported no metabolism of aminocyclopyrachlor in tall fescue at 192 HAT. Similar results of minimal (<25%) metabolism in tolerant species have been noted with picloram and triclopyr in barley, rice, and wheat (Braverman, 1995; Radosevich and Bayer, 1979; Sharma and Born, 1973).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolites of 14 C‐aminocyclopyrachlor were also not observed in the species L. serriola, C. solstitialis and C. juncea (Bell et al ., ) via TLC. In addition, they were also not observed in L. arundinaceum via HPLC (Lewis et al ., ). Bell et al .…”
Section: Discussionmentioning
confidence: 97%
“…As with other auxinic herbicides, the translocation of aminocyclopyrachlor occurs through the phloem (Bukun et al ., ). The absorption, translocation and metabolism of aminocyclopyrachlor can vary according to the sensitivity of the target plant (Bukun et al ., ; Bell et al ., ; Guerra et al ., ; Lewis et al ., ). The absorption and translocation of aminocyclopyrachlor has been studied in different weed species including Lactuca serriola L. , Centaurea solstitialis L. , Chondrilla juncea L. (Bell et al ., ), Cirsium arvense L. (Bukun et al ., ), Tecoma stans (L.) Juss.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations